Anatomical and carcass traits, partition of fat deposits, and meat quality in culled adult goats finished with high-fat diet - Oliveira, Felipe B. B. (2024)
The objective of this study was to examine the impact of a high-fat finishing diet on the in vivo performance, anatomical and carcass characteristics, and meat quality of adult culled goats. Over a period of 28 days leading up to slaughter, eighteen adult culled goats were subjected to a finishing diet provided in quantities sufficient to meet 3.0 times the nutritional requirements of adult non-dairy maintenance goats. The female goats were divided into two groups: one fed with the baseline diet without fat supplementation (n = 9) and the other fed a diet concentrated supplemented with whole full-fat linseed (n = 9). The diets varied in fat content (2.8% vs. 8.4% DM). The high-fat group exhibited a higher dry matter intake compared to the control group (+37%), along with elevated plasma cholesterol and triglyceride levels. The control group experienced a significant decrease in daily weight gain between the second and final week of the finishing period (-70%), in contrast to the increase observed in the high-fat group (+59%). At slaughter, no differences were noted between the groups in anatomical and carcass characteristics. Additionally, no differences were found between the diets regarding proximate composition, pH, yellow color component, and lightness of loin. The high-fat group exhibited a higher redness of loin. The inclusion of high-fat levels in finishing diets for culled adult goats allows for increased feed intake and performance but does not appear to affect carcass or meat quality.